Avaliação do potêncial de prateleiras de luz na distribuição da luz natural: estudo em modelo reduzido - Borba, Isabel Maria Melo (2005)
The purpose of the present dissertation is to organize systematically the study of adequate use of daylight by means of an element of passive architecture, the lightshelf, aiming at reducing electric energy consumption for artificial lighting in classrooms. This kind of solar shading element, placed at the upper part of a window, provides daylight control and its distribution, promoting a better visual perception, once there is sufficient daylight, qualitatively and quantitatively. Using a scale-model of a chosen classroom of the Centro Federal de Educação Tecnológica do Paraná, Curitiba, different situations were tested with a lightshelf. The used method comprehends following steps: illuminance measurements with digital luxmeters, in prefixed points inside the scale-model; simulation of solar exposition conditions, considering different periods of the day and of the year using sundials; analysis of different situations of lightshelves; data tabulation and analysis. These measurements were carried out in three phases: (1) a pre-test, aiming at testing the procedure; (2) measurements with horizontal lightshelves, comparing results with computer simulations with ECOTECT and RADIANCE; (3) innovative lightshelf types were proposed – concave, convex, concave/convex, and horizontal lightshelves with 25° tilt. Best configurations were studied graphically, with AUTOCAD 2002. As a result, it was noticed that the lightshelf might provide daylight more uniformly, reducing glare close to the window. Also, it was observed that with the innovative lightshelves, from the AUTOCAD study, there was even a daylight increase in the most distant points from the windows. According to the results, it can be proved that the direct sunlight may be used as a light source, once it is controlled by well-projected daylight systems.